Whose Knowledge?” Putting Politics Back Into Curriculum Choices for Refugees 1 - Kelcey, Jo (2019)
In 2012, the United Nations High Commissioner for Refugees (UNHCR) broke with longstanding policy and advocated that refugee students be taught the host state curriculum of their countries of asylum, rather than their home state curriculum. This study critically reflects on this policy shift by exploring the curriculum policies of the United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA). I analyze three points of tensions regarding the curriculum used in UNRWA’s schools to argue that the important political dimensions of curriculum have been overlooked in refugee education policy. This oversight has marginalized refugee perspectives in policy-making, with potentially negative consequences for education outcomes. Instead I argue in favor of curriculum policies for refugees that reflect the complex political realities of their displacement, exile and possibilities for return. This more nuanced approach can improve the relevance and quality of refugee education programs and is key to enhancing education’s protective role.